Blood nickel level and its toxic effect after transcatheter closure of persistent duct arteriosus using Amplatzer duct occluder - Mulyadi M. Djer; Bambang Madiyono (Indonesian Pediatric Society, 2009)
Background Transcatheter closure using amplatzer duct occluder(ADO) is currently the treatment of choice for patent ductusarteriosus (PDA). The ADO device is constructed from a Nitinolwire mesh containing 55% nickel. Up to now, there is still acontroversy about the effects of nickel contained in ADO.Objectives To determine blood nickel level at six months aftertranscatheter closure of PDA using ADO, toxic effects of nickelat six months after PDA closure using ADO, and the effects ofnickel on complete blood count (CBC), blood glucose and renalfunction.Methods Subjects were patients with PDA at IntegratedCardiovascular Services, Dr. Cipto Mangunkusumo Hospital,Jakarta. Routine blood test and blood nickel levels were measuredat the time of the procedure, and at the end of the first, third, andsixth months after intervention.Results There were 29 patients who underwent heart catheteri-zation and PDA closure using ADO. A time series analysis wasconducted on 23 patients who completed six-month follow-upafter the intervention. Median blood nickel level before procedurewas 58 ng/mL while at one, three and six months afterwards were60, 63 and 64 ng/mL respectively. The blood nickel levels didnot differ significantly between pre- and post-ADO. After PDAclosure, no toxic effects of nickel were found, both clinically andlaboratorically.Conclusions PDA closure using ADO has no effects on the nickellevels, CBC, blood glucose and renal function;